2023
DOI: 10.1007/s10661-023-11894-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between flue gas desulfurization gypsum and biochar on water infiltration characteristics and physicochemical properties of saline-alkaline soil

Peijun Wang,
Xiaolan Lin,
Qi Liu
et al.

Abstract: The application of flue gas desulfurization gypsum (FGDG) improves the soil structure, reduces soil pH, and accelerates soil salt leaching. Biochar amendment to soil can affect the soil infiltration rate, increase soil porosity, decrease soil bulk density, and enhance the water retention capacity. This study investigated the interactive effect of FGDG and biochar on water infiltration characteristics and physicochemical properties as well as determined the optimal amendment rate as a saline-alkaline soil condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…In our study, soil EC decreased following the application of biochar, bacteria, and biochar loaded with bacteria. Similar research demonstrated that the decreased soil EC may be related to the dissolution of soil salt by biochar [32]. Additionally, the decrease in soil EC post-bacterial application may be due to microbe metabolism that breaks down some of the salt [33].…”
Section: Discussionmentioning
confidence: 73%
“…In our study, soil EC decreased following the application of biochar, bacteria, and biochar loaded with bacteria. Similar research demonstrated that the decreased soil EC may be related to the dissolution of soil salt by biochar [32]. Additionally, the decrease in soil EC post-bacterial application may be due to microbe metabolism that breaks down some of the salt [33].…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, its effects on soil physical characteristics are primarily determined by its material composition in the short term [39], but its long term effects are indirectly influenced by affecting plant growth and the microbial community [14]. The biochar and the FGD gypsum have an impact on the soil ′ s physical parameters primarily due to their solid structure [40]. The biochar is capable of maintaining its structure for an extended period.…”
Section: Effects Of Amendments On Soil Quality Improvementmentioning
confidence: 99%